Evaluating the Impact of Remittance Flows, Financial Inclusion, and Macroeconomic Reserves on ASEAN-7 Economies - Rifki Khoirudin; Melani Januar Anindasari; Gea Dwi Asmara; Stanislaw Flejterski (Jurnal Ekonomi Pembangunan, 2025)
This study investigates the impact of remittances, domestic credit, export growth, consumer price index, and foreign exchange reserves on economic growth. Using annual data from the World Bank for the period 2014–2023, this study employs a fixed-effects panel data model approach and performs robust checks using FGLS to ensure robust and efficient panel data regression analysis. Empirical results indicate that remittances, domestic credit, export growth, and foreign exchange reserves are positive and statistically significant contributors to economic growth in the ASEAN region. Specifically, the findings highlight that a developed financial system enhances the growth-promoting effect of remittances by efficiently channeling capital into productive investment. In contrast, the consumer price index was found to have no significant direct impact on economic growth in this model, suggesting that moderate inflation serves more as a factor supporting macroeconomic stability than as a primary driver of real output. These findings highlight the importance of policymakers facilitating formal remittance management and expanding credit access for micro, small, and medium enterprises to stimulate innovation and employment. Furthermore, the study recommends prioritizing export-oriented industrialization and maintaining adequate foreign exchange reserves to strengthen regional economic resilience to global financial volatility.